General guidelines for the optimal economic aggregation of prosumers in energy communities. (1st November 2022) - Volpato, Gabriele; Carraro, Gianluca; Cont, Marco; Danieli, Piero; Rech, Sergio; Lazzaretto, Andrea
Abstract: Energy communities are regulatory tools promoting aggregations of users to foster the shift towards a renewable distributed generation. First in the literature, this paper addresses together three main aspects affecting the convenience of these aggregations: the complementarity between generation and demand of different prosumers, the criterion allocating the operating costs of energy communities, and the application of demand-response programs. The goal is quantifying the relative weight of these aspects using Mixed-Integer Linear Programming to minimize the operating costs of citizen and renewable energy communities, where prosumers are connected to the grid as single entity, or separately. Incentive- or price-based demand-response programs and a novel cost allocation criterion, which rewards the members with the highest economic benefit in passing from simple consumers to prosumers, are applied to each community configuration. Results allow identifying general guidelines for the optimal economic operation of energy communities: i) complementarity may reduce costs by 15–20%, ii) a fairer cost allocation criterion may reduce the bills of prosumers using free-of-charge renewables by 20–30% compared to those using dispatchable sources, and iii) price-based demand-response may reduce community costs beyond 50%. Eventually, directions of further research, as the impact of energy communities on a national power system, are drawn. Highlights: Three main aspects affect the aggregation of prosumers in energy communities. Optimal complementarity of prosumers allows to reduce costs in the range 15–20%. A novel cost allocation criterion for energy communities is proposed. Price-based demand response reduces the renewable energy community costs up to 60%. Citizen energy community has up to 39% lower costs than the renewable energy one.